Influence of alkali metal doping on selectivity behaviour of platinum catalysts for hydrogenation of 2-butyne-1,4-diol - Telkar, M. M.; Rode, C. V.; Rane, V. H.; Chaudhari, R. (Catalysis Communications, 2005)
Hydrogenation of 2-butyne-1,4-diol to 2-butene-1,4-diol (B(2)D) and butane-1,4-diol (B(1)D) using Pt catalysts doped with alkali metals was studied. These catalysts showed higher selectivity to the olefinic diol (B2D) compared to that with monometallic platinum catalyst. Among various alkali metals, Cs-doped catalyst showed highest selectivity (>99%) to B(2)D. The selectivity to B(2)D increased (up to 99.9%) with increase in the concentration of Cs from 0.25% to 1%. The increase in the basic strength of alkali doped catalysts measured by CO(2)-TPD, would be responsible for the increase in electron density of Pt hence, faster desorption and higher selectivity to the intermediate olefinic diol (B(2)D). The reaction parameters; such as temperature, H(2) pressure and substrate concentration haye strong influence on the catalyst activity but almost no effect on the selectivity to B(2)D. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; platinum catalysts; Selective hydrogenation